Twenty Years of Airborne Water Vapor and Total Water Measurements of a Diode Laser Based Photoacoustic Instruments - Szakáll, Miklós; Mohácsi, Árpád; Tátrai, Dávid; Szabó, Anna; Huszár, Helga; Ajtai, Tibor; Szabó, Gábor; Bozóki, Zoltán (Frontiers in Physics, 2020)
We present relevant issues collected over 20 years of development and operation of an airborne water vapor/total water detector based on photoacoustic spectroscopy. The WaSul–Hygro instrument possesses high selectivity, short response time, and wide dynamic range, which are key requirements against trace gas measurement systems for applications in atmospheric sciences. Besides the major properties of WaSul–Hygro, we discuss our efforts to develop a robust instrument that has proven its long-term reliability over the last 15 years operating onboard a commercial aircraft within the framework of the CARIBIC project.